Mutation of Gly195 of the ChlH Subunit of Mg-chelatase Reduces Chlorophyll and Further Disrupts PS II Assembly in a Ycf48-Deficient Strain of Synechocystis sp. PCC 6803 - Crawford, Tim S.; Eaton-Rye, Julian J.; Summerfield, Tina C. (Frontiers in Plant Science, 2016)
Biogenesis of the photosystems in oxygenic phototrophs requires co-translational insertion of chlorophyll a. The first committed step of chlorophyll a biosynthesis is the insertion of a Mg2+ ion into the tetrapyrrole intermediate protoporphyrin IX, catalyzed by Mg-chelatase. We have identified a Synechocystis sp. PCC 6803 strain with a spontaneous mutation in chlH that results in a Gly195 to Glu substitution in a conserved region of the catalytic subunit of Mg-chelatase. Mutant strains containing the ChlH Gly195 to Glu mutation were generated using a two-step protocol that introduced the chlH gene into a putative neutral site in the chromosome prior to deletion of the native gene. The Gly195 to Glu mutation resulted in strains with decreased chlorophyll a. Deletion of the PS II assembly factor Ycf48 in a strain carrying the ChlH Gly195 to Glu mutation did not grow photoautotrophically. In addition, the ChlH-G195E:ΔYcf48 strain showed impaired PS II activity and decreased assembly of PS II centers in comparison to a ΔYcf48 strain. We suggest decreased chlorophyll in the ChlH-G195E mutant provides a background to screen for the role of assembly factors that are not essential under optimal growth conditions.